Pharmacological and physiological properties of the after-hyperpolarization current of bullfrog ganglion neurones. - Goh, J W (1987)
1. The slowly decaying, calcium-dependent after-hyperpolarization (a.h.p.) that follows action potentials in bullfrog ganglion B cells has previously been shown to be generated by a potassium current called IAHP. We have recorded IAHP using a switched, single-electrode hybrid clamp where current-clamp mode was changed to voltage-clamp mode immediately after repolarization of a spike or the last spike of a train. 2. Reduction of extracellular calcium reduced the decay time of IAHP following a single spike. At all levels of extracellular calcium tested (0.5-4 mM), the decay time of IAHP was longer following a train of action potentials than following a single action potential. Thus, the time course of IAHP evoked by action potentials is a function of the calcium load induced by the action potentials. Conversely, agents that reduce the amount of IAHP activated without affecting its rate of decay, probably do not affect calcium influx. 3. Muscarine (2 or 10 microM) inhibits IAHP following an action potential by at most 30% and has no effect on decay rate of IAHP. These results suggest that muscarine has little or no effect on either calcium influx or sequestration. Decay of the a.h.p. is accelerated by muscarine but this effect is due to an increased leak conductance. 4. Charybdotoxin (CTX) between 4 and 20 nM, prolongs action potential duration in a manner consistent with blockade of the voltage- and calcium-dependent potassium current (Ic) involved in spike repolarization in these cells. This action is consistent with its reported action on analogous channels in other systems. However, CTX also reduces IAHP. Thus, in bullfrog ganglion neurones, two distinct calcium-dependent potassium currents exhibit a comparable sensitivity to CTX. This cannot be due to a decreased influx of calcium because the decay rate of IAHP following an action potential is unchanged. The action of CTX was observed with both crude and purified preparations of CTX. 5. Apamin (25 nM) and (+)-tubocurarine (concentration giving 50% of maximal inhibition = 20 microM) block IAHP without affecting action potential duration. The action of (+)-tubocurarine is more readily reversible than apamin. Approximately 20% of IAHP is resistant to blockade by either apamin or (+)-tubocurarine. 6. Muscarine was used to block the M-current (IM) selectively and (+)-tubocurarine was used to inhibit IAHP selectively. Both currents were shown to contribute to spike frequency adaptation. Inhibition of both IM and IAHP has a synergistic action to increase repetitive firing.